The Moderating Effect of Income on Penalty Waivers, BBN Exemptions, and Service Quality on Taxpayer Compliance: - - I Gusti Agung Geg Puspa Dewi; Sri Ernawaty; Soelistijono Boedi; Gemi Ruwanti (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2026)
This study aims to analyze and obtain empirical evidence on the effect of penalty waiver, BBN exemption, and service quality on motor vehicle taxpayer compliance, with income as a moderating variable. This study uses qualitative data in the form of numerical responses from completed questionnaires. Sampling in this study used a purposive sampling method with the Slovin formula, with a population of 128,357 taxpayers with two or more wheels and a margin of error of 10% (0.1), resulting in 100 motor vehicle taxpayers who actively pay their taxes and reside at the Banjarbaru Samsat UPPD. The variables in this study were penalty waiver, BBN exemption, service quality, and income. Hypothesis testing used MRA (Moderated Regression Analysis) and Partial Test (t-test). The results showed that penalty waiver and service quality had a positive and significant effect on taxpayer compliance. Meanwhile, the BBN exemption had a positive but insignificant effect. Income did not moderate the relationships among penalty waiver, BBN exemption, service quality, and taxpayer compliance